2001
DOI: 10.1093/glycob/11.5.365
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated human milk oligosaccharides vary between individuals and over the course of lactation

Abstract: Specific human milk oligosaccharides, especially fucosylated neutral oligosaccharides, protect infants against specific microbial pathogens. To study the concentrations of individual neutral oligosaccharides during lactation, a total of 84 milk samples were obtained from 12 women at 7 time periods during weeks 1-49 postpartum. The neutral oligosaccharides from each sample were isolated, perbenzoylated, resolved, and quantified by reversed-phase high-performance liquid chromatography. The resultant oligosacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
304
2
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(342 citation statements)
references
References 25 publications
26
304
2
10
Order By: Relevance
“…In one study, a decrease in the total concentration of oligosaccharides was observed from the first weeks postpartum to about half the concentration after one year. In the same report, the absolute and relative concentrations of HMOs between individual donors and at different stages of lactation varied significantly [22]. Asakuma et al [24] analyzed the level of several neutral oligosaccharides in human milk colostrums for 3 consecutive days from 12 Japanese women.…”
Section: Milk Oligosaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, a decrease in the total concentration of oligosaccharides was observed from the first weeks postpartum to about half the concentration after one year. In the same report, the absolute and relative concentrations of HMOs between individual donors and at different stages of lactation varied significantly [22]. Asakuma et al [24] analyzed the level of several neutral oligosaccharides in human milk colostrums for 3 consecutive days from 12 Japanese women.…”
Section: Milk Oligosaccharidesmentioning
confidence: 99%
“…Characterization of HMO has been accomplished using HPAEC and HPLC in combination with derivatization techniques [4,[21][22][23][24]. The identification of HMOs was based on the retention time of commercially available milk oligosaccharide standards and their quantification was relative to the amount of standards.…”
Section: Milk Oligosaccharidesmentioning
confidence: 99%
“…As a result, a breast-fed infant is expected to be at variable risk of infectious diarrhea depending on his/her intestinal expression of H antigens and his/her mother secretion of the same molecule in milk; in this scenario, maximization of FUT2 expression in lactating epithelia might be extremely important in providing immunization to newborns. Indeed, different oligosaccharide species in human milk form part of the innate immune system with activity against different pathogens (Newburg et al 2005), and fucosyloligosaccharides containing alpha (1,2)-linked fucose are prevalent (Chaturvedi et al 2001). Women who are nonsecretors do not express measurable 2-linked fucosyloligosaccharides and the amount of milk fucosyloligosaccharides varies even among secretors (Chaturvedi et al 2001), possibly suggesting the presence of genotype differences responsible for such variation (Chaturvedi et al 2001).…”
Section: Fut2 (Lewis System)mentioning
confidence: 99%
“…Indeed, different oligosaccharide species in human milk form part of the innate immune system with activity against different pathogens (Newburg et al 2005), and fucosyloligosaccharides containing alpha (1,2)-linked fucose are prevalent (Chaturvedi et al 2001). Women who are nonsecretors do not express measurable 2-linked fucosyloligosaccharides and the amount of milk fucosyloligosaccharides varies even among secretors (Chaturvedi et al 2001), possibly suggesting the presence of genotype differences responsible for such variation (Chaturvedi et al 2001). Since diarrhea represents a very common cause of mortality in newborns throughout the world, the adaptive significance of decreasing the chance of infection in breast-fed infants is evident.…”
Section: Fut2 (Lewis System)mentioning
confidence: 99%
“…Concentration and composition of OS in human milk differ considerably among individuals and during the course of lactation [118] and contains more than 130 different oligosaccharides at a concentration of 15-23 g/L in colostrum and 8-12 g/L in transitional and mature milk [119,120]. Prebiotics are introduced in infant formulae with the objective of obtaining a bifidogenic effect identical to breast-fed infants [121] and inclusion of OS may beneficially modify the composition of the gut microbiota of formula-fed infants [122] and in immunomodulation [119] by acting as a receptor for bacteria and viral adhesion molecules [123] and stimulate the bifidus flora in the colon [124].…”
Section: • Lipid Lowering Actionmentioning
confidence: 99%